2017
DOI: 10.1089/mdr.2016.0064
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Frequency in Species of Nontuberculous Mycobacteria in Kermanshah Drinking Water Supplies Using the PCR-Sequencing Method

Abstract: In this study, we recognized the evidence of contamination by nontuberculous mycobacteria in corroded water pipes. As a result of the high prevalence of these bacteria in drinking water in Kermanshah, this is important evidence of transmission through drinking water. This finding can also help public health policy makers control these isolates in drinking water supplies in Kermanshah.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
12
2
Order By: Relevance
“…1 Our data show that 16S rRNA gene sequencing, as a single identification target, cannot be used an efficient method for the identification of closely-related mycobacterium species such as M. abscessus, M. bolletii or M. massiliense also pathogenic M. kansasii was easily differentiated from nonpathogenic M. gastri by rpoB analysis; this differentiation cannot be achieved by using 16S rRNA gene sequences. 18 In contrast to our study, Azadi et al 19 reported that the three most prevalent species of NTM in hospital water system were M. lentiflavum (28.2%), M. paragordonae (21.1%), and M. fredriksbergense (9.8%). In America and most parts of Europe, M. avium complex was the most common of NTM, in this regard in a study conducted by Molicotti in Sassari (Italy), 6 M. avium and M. gordonae had the highest frequency among NTM.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…1 Our data show that 16S rRNA gene sequencing, as a single identification target, cannot be used an efficient method for the identification of closely-related mycobacterium species such as M. abscessus, M. bolletii or M. massiliense also pathogenic M. kansasii was easily differentiated from nonpathogenic M. gastri by rpoB analysis; this differentiation cannot be achieved by using 16S rRNA gene sequences. 18 In contrast to our study, Azadi et al 19 reported that the three most prevalent species of NTM in hospital water system were M. lentiflavum (28.2%), M. paragordonae (21.1%), and M. fredriksbergense (9.8%). In America and most parts of Europe, M. avium complex was the most common of NTM, in this regard in a study conducted by Molicotti in Sassari (Italy), 6 M. avium and M. gordonae had the highest frequency among NTM.…”
Section: Discussioncontrasting
confidence: 99%
“…17 In contrast with our previous study on frequency in species of NTM in Kermanshah drinking water supplies, we found following NTM isolates; M. goodii, M. aurum, and M. gastri were the most prevalent species (11.5%) and we not found M. simiae and M. fortuitum in drinking water supplies. 18 In contrast to our study, Azadi et al 19 reported that the three most prevalent species of NTM in hospital water system were M. lentiflavum (28.2%), M. paragordonae (21.1%), and M. fredriksbergense (9.8%). Another study of 14 provinces in Iran by Velayati and his colleagues showed that M. simiae is the most common species.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies conducted in Japan revealed that the draft genome sequence of Mycolicibacterium peregrinum isolated from a pig affected with lymphadenitis shares close identity with that of Mycolicibacterium peregrinum isolated from the soil of the pig's environment (Komatsu et al 2019). Moreover, the fact that Mycolicibacterium peregrinum was isolated from other animals (e.g., lion; Panthera leo), and from drinking water (Gcebe and Hlokwe 2017;Mohajeri et al 2017) indicates that Mycolicibacterium peregrinum can inhabit several environments. In our study, the rpoB gene of the Mycolicibacterium peregrinum isolated from wildlife showed 100% similarity to that of Mycolicibacterium peregrinum isolated from drinking water (Mohajeri et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…M. mucogenicum was also detected in a similar study by Nasr Esfahani et al [21] in central Iran, where the dominant isolates were M. fortuitum, M. chelonae-like organism, and M. mucogenicum. A similar study by Mohajeri et al [22] evaluating the frequency of NTM in drinking water supplies revealed NTM in 32% of 110 samples, with M. gastri as the most common species.…”
Section: Discussionmentioning
confidence: 52%